\(\Leftrightarrow\left(x^4+5x^2+6\right)\left(x^4+5x^2+4\right)-24\)
Đặt \(x^4+5x^2+6=t\)
\(t\left(t-2\right)-24=t^2-2t-24\)
\(\Leftrightarrow t^2-2t+1-25=\left(t-1\right)^2-5^2=\left(t-6\right)\left(t+4\right)>0\)
TH1 : \(\left\{{}\begin{matrix}t-6>0\\t+4>0\end{matrix}\right.\Leftrightarrow t>6\)
TH2 : \(\left\{{}\begin{matrix}t-6< 0\\t+4< 0\end{matrix}\right.\)<=> t < -4
Theo cách đặt \(x^4+5x^2+6>6\Leftrightarrow x^2\left(x^2+5\right)>0\)* luôn đúng *
\(x^4+5x^2+6< -4\Leftrightarrow x^4+5x^2+10< 0\)
\(\Leftrightarrow x^4+\dfrac{2.5}{2}x^2+\dfrac{25}{4}+\dfrac{15}{4}< 0\Leftrightarrow\left(x^2+\dfrac{5}{2}\right)^2+\dfrac{15}{4}< 0\)( vô lí )